THE ACTIVITY OF HUMAN RED BLOOD CELLS CARBONIC ANHYDRASE AS CATALYST FOR CARBON DIOXIDE HYDRATION - Sabrina Valencia, Kesya
One of the attempt to mitigate global warming (the greenhouse effect) is the hydration of carbon dioxide. In the human body, the reaction of carbon dioxide hydration is catalyzed by carbonic anhydrase present in red blood cells. This research aims to determine the activity of red blood cell carbonic anhydrase in converting carbon dioxide to bicarbonate in vitro, with the goal of developing an effective and efficient technology to reduce carbon dioxide gas levels. The research stages including isolating carbonic anhydrase from red blood cells, purifying carbonic anhydrase through chromatography, identifying carbonic anhydrase using SDS-PAGE, and testing the catalytic activity of carbonic anhydrase using Wilbur-Anderson method. The results show that red blood cells, which are biconcave in shape, yield a red color crude enzyme extract (hemoglobin) with a total protein concentration of 0.292 mg/mL. Carbonic anhydrase in the crude extract was identified by the presence of a protein band with a molecular weight of approximately 30 kDa. Hemoglobin contaminants were identified as dimers with a molecular weight of approximately 30-35 kDa. The spesific activity of carbonic anhydrase in the crude extract without dilution was 9247 Units/mg while with a 10 fold-dilution it was 42808 Units/mg. Measurement errors occured in the undiluted crude extract due to correlation coefficient of only 0.868. The crude enzyme containing carbonic anhydrase is then purified using a sulfate precipitation method to obtain pure carbonic anhydrase.